Layering Charged Polymers Enable Highly Integrated High‐Capacity Battery Anodes - Han, Dong‐Yeob; Han, Im Kyung; Son, Hye Bin; Kim, Youn Soo; Ryu, Jaegeon; Park, Soojin (Advanced functional materials, 2023)
High‐capacity anode materials are promising candidates for increasing the energy density of lithium (Li)‐ion batteries due to their high theoretical capacities. However, a rapid capacity fading due to the huge volume changes during charge‐discharge cycles limits practical applications. Herein, a layering‐charged polymeric binder is introduced that can effectively integrate high‐capacity anodes using a strong yet reversible Coulomb interaction and enriched hydrogen bonding. The charged polymeric binder builds a dynamically charge‐directed network on the active materials with high versatility and efficiently dissipates the electrode stress with its excellent mechanical properties. In addition, poly(ethylene glycol) (PEG) moieties of the charged binder offer a fast Li‐ion conduction pathway that can form an ultra‐thick silicon oxide (SiOx)‐based electrode (≈10.2 mAh cm−2) without compromising the reversible specific capacity and promote effective charge interaction as a mechanical modulator. Such an unprecedented charge‐directed binder provides insights into the rational design of a binder for high‐capacity anodes. A layering‐charged polymeric binder forms charge‐directed network on the high‐capacity anodes which efficiently dissipates the stress of the electrode using a strong yet reversible Coulomb interaction and enriched hydrogen bonding. Poly(ethylene glycol) (PEG) moieties, as a mechanical modulator, in charged polymer facilitate the Li‐ion conduction which enable the formulation of an ultrathick silicon oxide (SiOx)‐based electrode (≈10.2 mAh cm−2).